Corporate social responsibility and sustainable development in the context of environmental challenges - D. V. Voyko; A. V. Voyko (Вестник университета)
The article discusses the interconnection of corporate social responsibility and sustainable development of companies considering climate changes. Corporate sustainable development imposes attention to environmental problems that makes companies to switch to environmentally friendly technologies, reducing carbon emission, cutting natural sources’ deployment. The main goal of the article is to research if there are different strategies may be applied to shift companies’ activities to environmentally friendly mode. Different opinions and points of view were introduced within the article and confirm the importance of corporate social responsibility. According to corporate cases of corporate social responsibility implementation several principles were elaborated to manage environmental issues. As a result, actual business practices were observed through the principles of corporate social responsibility so, that an average strategy of companies’ sustainable development was described. There is a conclusion in the article, that corporate social responsibility can’t be applied within the company’s activity without dealing with sustainable development, because the responsibility appears as a tool of sustainability, but not the independent purpose. It has been outperformed that social responsibility within environmental issues takes significant place in strategies of sustainable development in present time and even overshadows the issue of financial achievements increase.